In Silico Screening Anticancer of Six Triterpenoids toward miR-494 and TNF-α Targets - Vikra Ardiansyah Zaini; Purwantiningsih Sugita; Luthfan Irfana; Suminar Setiati Achmadi (Jurnal Kimia Sains dan Aplikasi, 2020)
Hepatocellular carcinoma (HCC) accounts for up to 90% of all primary liver cancers worldwide. Cinobufagin is recognized to inhibit miR-494 as the HCC target. Increased expression of TNF-α results in an inadequate response to liver anticancer drugs. The models in this study were cinobufagin, cycloartenol, and ethyl acetate fractions of Ganoderma lucidum, 2–5. Seven docking targets in this study were Akt, ERK1, ERK2, PI3K, TNF-α, TNFR1, and TNFR2. Cycloartenol and compound 4 comply with Veber’s rules, Lipinski’s rule of 5, and demonstrate moderate toxicity. The action implies a potential docking target since it produces bond affinities with the compound 2–5 that agree with the IC50 in the literature, which is based on in vitro experiments. Akt as a receptor target is AZD5363. Cycloartenol shows a low ability to inhibit Akt. Conversely, compound 4 inhibits the Akt better than that of cycloartenol, although it is not as good as cinobufagin and AZD5363. Therefore, compound 4, a triterpenoid with a basic framework of lanostane has the potential to be an anticancer candidate for the liver.